2011
DOI: 10.1038/bjc.2011.221
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus microRNAs and lung cancer

Abstract: Background:We conducted the first analysis of viral microRNAs (miRNAs) in lung cancer, with a focus on Epstein–Barr virus (EBV).Methods:We evaluated viral miRs with a two-channel oligo-array targeting mature, anti-sense miRNAs in 290 cases. In 48 cases, we compared microarray and real-time quantitative PCR (qPCR) expression for three EBV miRNAs. We tested for EBV DNA, RNA, and protein in tumour tissue from six cases with and six cases without strong qPCR-based evidence of EBV miRNAs.Results:The EBV miRNAs stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…Contrasting to Koshiol et al 5 we were unable to differentiate lung tumor histology with airways EBV positivity. However, we did not support previous studies showing correlations between EBV and disease stage.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrasting to Koshiol et al 5 we were unable to differentiate lung tumor histology with airways EBV positivity. However, we did not support previous studies showing correlations between EBV and disease stage.…”
Section: Discussioncontrasting
confidence: 99%
“…Several infectious agents such as viruses, bacte-ria, and fungi have already been identified as being involved in lung cancer. [5][6][7] The EBV is a herpes virus classified as a group 1 carcinogen by the International Agency for Research in cancer. 4 Several other viruses have been suspected to be involved in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…38 However, studies from the west have reported either a complete lack or a very low prevalence of EBV in lung carcinoma. 12,[39][40][41][42][43][44] The reported seroprevalence of CMV ranges from 50 to 90% in different countries of the world. 12 In the present study, 2 cases (2.7%) of lung carcinoma showed positivity for EBV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency between platforms is not uncommon due to technical differences in sensitivity and specifi city of the different assays, the amount and quality of RNA available, or biologic differences of the target molecules. 30 Furthermore, the corresponding gene product (ie, protein) could be quantifi ed, as a change in gene expression level does not always equate to a change in function.…”
Section: Discussionmentioning
confidence: 99%